Electrochemically grown nanoporous MnO2 nanowalls on a porous carbon substrate with enhanced capacitance through faster ionic and electrical mobility - Anothumakkool, Bihag; Kurungot, Sreekumar (Chemical Communications, 2014)
We report the deposition of uniform porous MnO2 nanowalls on a conducting carbon fiber substrate using a simple electrochemical method, which produces ordered nano-channels demarcated by the MnO2 walls for easy ion transport and a continuous electron path created by the carbon backbone. The system achieves a specific capacitance of 1149 F g(-1) and retains 565 F g(-1) even at dragging conditions as high as 100 A g(-1).